Ufarlige forbindelser? - Svein Vatsvåg Nielsen (Primitive Tider, 2014)
The article discusses the role of rigid methodology in the archaeological theoretical debate by focusing on the potential of the theoretical philosophy of Immanuel Kant. This tradition is defined in its relation to empiricism through a critique of theoreticism. Further on, two archaeological texts, one focusing on postprocessual and the other on symmetrical archaeology, are analyzed in order to fully understand their inherent metaphysics. It is argued that both texts maintain a pre-critical understanding of Kantian philosophy, and that this point is vital to their main arguments. In the end, the author argues for the potential of Kantian philosophy for a better understanding of archaeological theory.